Modificação do PEUAMM com PEG para obtenção de nanocompósitos com nanofibras de carbono - Hortencio, Johnnys da Silva (2019)
The preparation of composites and polymeric nanocomposites with fillers has been a means of obtaining materials that help to improve the performance of the polymeric materials. The nanofiller appeared with great potential for use in nanocomposites polymeric due to their mechanical and thermal properties. In this work, compositions of UHMWPE/PEG and polymer nanocomposites with carbon nanofibers (CNF) were prepared by grinding the powders in order to evaluate the modifications promoted by the incorporation of PEG in the UHMWPE. Then, the UHMWPE/PEG compositions and the nanocomposites were compression molded by the sequential application of pressures of 3, 6 and 9 ton, alternating every 4 minutes at a temperature of 160 ° C. In addition, we investigated the addition of carbon nanofibers in the matrix of UHMWPE/PEG through the mechanical and thermal properties. The mills were made in two sorts of mills (high-energy mill and jar mill). The high-energy mill was used for the processing of the UHMWPE/PEG mixtures with concentrations of 4, 8 and 12% (w/w) PEG. For the nanocomposites, the jar mill was used with concentrations of 0. 5, 1.0 and 1.5 % (w/w) NFC for a period of 24 hours. All samples were described by Differential Scanning Calorimetry (DSC), Thermogravimetric Analysis (TGA), Scanning Electron Microscopy (SEM) and tensile mechanics tests. The results showed that there was a good distribution of the PEG in the UHMWPE, so that its mechanical properties were not altered with the addition of PEG. On the other hand, the thermal properties of the UHMWPE/PEG compositions were improved in terms of the degree of crystallinity and the initial and maximum degradation temperatures, especially the blended compositions in the pitcher mill. Regarding the nanocomposites, the DSC test showed that with increasing CNF concentration in the matrix, the degree of crystallinity decreased. In the TGA analysis, the addition of CNF improved the thermal stability of the matrix, and the mass losses remained in a single step. In relation to the mechanical and thermal properties of the nanocomposites, the CNFs were not so efficient, causing a decrease in these properties of the UHMWPE/12%PEG/24h mixture, due to the dispersion of the nanofibers being inefficient, as well as the formation of CNF agglomerates in the polymer matrix.